Perceived Factors Influencing Emotional Intelligence among Adolescents - Ofili, Irene A. (ESUT JOURNAL OF SOCIAL SCIENCES, 2022)
The study investigated perceived factors influencing emotional intelligence among adolescents. A total of 128 participants comprising 57 males and 71 females were selected from students’ population of Ozalla High School Ozalla in Nkanu West Local Government Area of Enugu State. The participants were selected from senior secondary school students in class two (SS 2) making use of available sampling technique. They are within the ages of 15 – 22 years, with a mean age of 18.1 and a standard deviation of 1.7. A 33 – item of self-referencing statements developed by Schutte et al. (1998) was used to measure Emotional Intelligence. A cross sectional design was adopted while Chi square as a statistic was applied to analyze the data. Results showed that a significant influence of recognition of emotions as a perceived factor influencing emotional intelligence among adolescents was observed, X2 (df,1) = 48 at p<.001; also a significant influence of facial expression as a perceived factor influencing emotional intelligence among adolescents was observed X2 (df,1) = 7.26 at p<.01; and a significant influence of positive mood as a perceived factor influencing emotional intelligence among adolescents was observed, X2 (df,1) = 48 at p<.001. The findings were discussed in relation to literatures reviewed and suggestions made.